Probing the origin of ultra-high-energy cosmic rays with neutrinos in the EeV energy range using the Pierre Auger Observatory - Aab, A.; Abreu, P.; Aglietta, M.; Albuquerque, I. F. M.; Albury, J. M.; Allekotte, Ingomar; Almela, Daniel Alejandro; Alvarez Castillo, Maria Belen; Alvarez Muñiz, J.; Anastasi, G. A.; Anchordoqui, Luis A.; Andrada, María Belén; et al. (IOP Publishing, 2019)
Fil: Aab, A.. Radboud Universiteit Nijmegen; Países Bajos